The Effectiveness of PowToon Learning Media on the Writing Ability of Sundanese Script - Jatnika, Tyas Harsa; Ropiah, Opah (Universitas Muhammadiyah Ponorogo, 2024)
Learning media play a crucial role in addressing the challenge of students' inability to write Sundanese scripts. The PowToon application offers various features that support the creation of learning media, making it a viable alternative in technological advancement. The purpose of this study is to assess the effectiveness of utilizing PowToon as a learning tool to improve the Sundanese script writing skills of class VII students at MTs Negeri 3 Kuningan. A quantitative approach with a one-group pretest-posttest design was employed in this research, which took place at MTs Negeri 3 Kuningan using class VII-2 as the sample group. The results indicate an improvement in the students' ability to compose Sundanese scripts, as supported by the findings of hypothesis testing. The average student score before using the PowToon application learning media was 47.85, while after using the PowToon application learning media the average score was 82.29. Apart from that, the results of the hypothesis test, Sig. (2-tailed), 0.000 ; 0.05. Therefore, Ha is accepted and Ho is rejected. So the effectiveness of the PowToon application learning media on the ability to write Sundanese script has proven effective for use in learning. This is characterized by a significant difference in students' learning outcomes for writing Sundanese script before and after using the PowToon application learning media.